Complications of Pediatric Mandibular Distraction Osteogenesis Hardware: A 10-Year Retrospective Analysis of the Food and Drug Administration Manufacturer and User Facility Device Experience Database. Issue 3 (September 2022) - Jinka, Sanjay K.A.; Coombs, Demetrius M.; Murthy, Ananth S.
Background: The United States Food and Drug Administration's (FDA) Manufacturer and User Facility Device Experience (MAUDE) database provides access to device related adverse event reports. This database mandates national reporting of complications that lead to "death and serious injury" by manufacturers, importers, and device user facilities. This study used MAUDE to conduct post-market surveillance of pediatric mandibular distraction osteogenesis (MDO) hardware. Methods: A MAUDE database search with terms related to mandibular distraction was performed for report dates between October 1st, 2011, and October 1st, 2021. Duplicate reports, reports from literature reviews, and vague reports were removed. Manufacturers were contacted to establish which devices were pediatric-use-only. Adult-use and mixed-use devices were excluded. Each remaining report was manually reviewed/categorized to compile summative data. Results: Seventy pediatric-use-only device reports were identified. The damaged/non-functioning part of the device included the distractor itself (57.14% of reports), footplate(s) (37.14%), or screw(s) (5.71%). Intraoperative and postoperative complications made up 15.71% and 84.29% of reports, respectively. Twenty percent of complications occurred during the activation phase and 1.43% occurred during device removal. The most common report was failure of the device to advance (37.14% of total complications). Some form of operative treatment or explantation was performed for 51.43% and 34.29% of complications, respectively. External distractors and related hardware made up 8.6% of reports and the most common complication in this group was the screw backing out at 33.3% of all reports. Conclusions: The MAUDE database is a useful tool in evaluation of MDO device-related incidents. Most complications occur in the postoperative period, during the distraction phase, and often require device removal. The most common complication in external distractors was screws backing out. Mindful activation of the distractor, careful device/screw handling, technical improvement of the devices, and thorough preoperative planning may minimize these untoward events.